Biochemical evidence that human EB1 does not bind preferentially to the microtubule seam. Issue 6 (23rd April 2013) - Alberico, Emily O.; Lyons, Daniel F.; Murphy, Ryan J.; Philip, Julia T.; Duan, Aranda R.; Correia, John J.; Goodson, Holly V.
<x xml:space="preserve">Abstract</x> EB1 is a highly conserved microtubule (MT) plus end tracking protein (+TIP) involved in regulating MT dynamics, but the mechanisms of its effects on MT polymerization remain undefined. Resolving this question requires understanding how EB1 interacts with MTs. Previous electron microscopy of the S. pombe EB1 homolog Mal3p suggested that Mal3p binds specifically to the MT seam, implying that EB1 family members promote MT polymerization by stabilizing the seam. However, more recent electron microscopy indicates that Mal3p binds everywhere except the seam. Neither set of experiments investigated the behavior of human EB1, or provided an explanation for why these studies arrived at different answers. To resolve these questions, we have used a combination of MT‐binding assays and theoretical modeling with MTBindingSim. Our results indicate that human EB1 binds to the lattice, consistent with the recent Mal3p results, and show that Mal3p‐binding assays that were previously interpreted as evidence for preferential seam binding are equally consistent with weak lattice binding. In addition, we used analytical ultracentrifugation to investigate the possibility that the EB1 monomer–dimer equilibrium might contribute to EB1 binding behavior, and determined that the EB1 dimerization dissociation constant is approximately 90 nM. We and others find that the cellular concentration of EB1 is on the order of 200 nM, suggesting that a portion of EB1 may be monomeric at physiological concentrations. These observations lead us to suggest that regulation of EB1 dimerization might play a role in controlling EB1 function. © 2013 Wiley Periodicals, Inc